2016
DOI: 10.1038/mi.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Macrophages are critical to the maintenance of IL-13-dependent lung inflammation and fibrosis

Abstract: The roles of macrophages in type 2-driven inflammation and fibrosis remain unclear. Here, using CD11b-Diphtheria Toxin Receptor (DTR) transgenic mice and three models of IL-13-dependent inflammation, fibrosis, and immunity, we show that CD11b+ F4/80+ Ly6C+ macrophages are required for the maintenance of type-2 immunity within affected tissues but not secondary lymphoid organs. Direct depletion of macrophages during the maintenance or resolution phases of secondary S. mansoni egg-induced granuloma formation cau… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
98
1
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 113 publications
(109 citation statements)
references
References 49 publications
3
98
1
2
Order By: Relevance
“…However, the contribution of macrophages to the development and maintenance of IL-13-dependent fibrosis is less clear as macrophages are not thought to be a major source of IL-13 (Wynn, 2004). To investigate the role of macrophages in a model of IL-13 driven fibrosis, Borthwick and colleagues have employed CD11b-DTR mice and depleted CD11b + monocytes and macrophages at different time points in three models of type-2 cytokine-driven disease (Borthwick et al, 2015). Here, monocyte and macrophage but not dendritic cell depletion during the maintenance and resolution phases caused a profound decrease in inflammation, fibrosis, and type 2 gene expression in the tissues but not in secondary lymphoid organs, suggesting that macrophages are critical to the maintenance of type 2 inflammation in the injured lung.…”
Section: Regulation and Function Of Pro-fibrotic Macrophagesmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the contribution of macrophages to the development and maintenance of IL-13-dependent fibrosis is less clear as macrophages are not thought to be a major source of IL-13 (Wynn, 2004). To investigate the role of macrophages in a model of IL-13 driven fibrosis, Borthwick and colleagues have employed CD11b-DTR mice and depleted CD11b + monocytes and macrophages at different time points in three models of type-2 cytokine-driven disease (Borthwick et al, 2015). Here, monocyte and macrophage but not dendritic cell depletion during the maintenance and resolution phases caused a profound decrease in inflammation, fibrosis, and type 2 gene expression in the tissues but not in secondary lymphoid organs, suggesting that macrophages are critical to the maintenance of type 2 inflammation in the injured lung.…”
Section: Regulation and Function Of Pro-fibrotic Macrophagesmentioning
confidence: 99%
“…Related studies have also identified the chemokine receptor CCR8 as a major mediator of macrophage recruitment to injured liver, with CCL1-directed migration controlling the recruitment of classical inflammatory monocytes that promote TGF-β1-dependent fibrosis induced by CCL4 or bile duct ligation (Heymann et al, 2012). Thus, in addition to producing important pro-fibrotic mediators like TGF-β1 (Figure 2), monocytes and macrophages can also promote fibrosis indirectly by orchestrating local inflammatory reactions that maintain fibrotic responses or by blocking the emergence of pro-resolution pathways (Borthwick et al, 2015; Ehling et al, 2014; Mitchell et al, 2009). …”
Section: Regulation and Function Of Pro-fibrotic Macrophagesmentioning
confidence: 99%
“…For example, M2-derived factors including Fizz1/Relmα and Arginase-1 have been shown to limit IL-13-dependent fibrotic repair processes such as collagen deposition, eosinophil infiltration, CD4 + T cell activation, and granuloma formation (Wynn, 2015). During a properly regulated response, these M2 cells can also receive additional signals from the local environment that transition them towards a phenotype capable of remodeling newly deposited extracellular matrix components through the production of tissue proteases (Borthwick, et al, 2016, Novak and Koh, 2013). It is possible that a dysregulation of these macrophage-coordinated repair mechanisms establishes a detrimental cycle that is the basis for the destructive lung pathology observed in progressive emphysema as illustrated in Figure 4.…”
Section: Proposed Model Of Immunopathology In Emphysemamentioning
confidence: 99%
“…Nevertheless, the mechanisms that govern tissue regeneration versus pathological type-2 cytokine-driven fibrosis remain unclear. While previous studies have implicated M2 macrophages in repair and fibrosis (Borthwick et al, 2015; Chen et al, 2012), other cells including hepatocytes, cholangiocytes, HPCs, and fibroblasts also express functional IL-4 and IL-13 receptors, yet their roles in the progression of liver disease, steatosis, fibrosis, DR, and liver regeneration during chronic type-2 cytokine-driven inflammatory responses have remained unclear. Moreover, while clinical studies have found elevated type-2 cytokines and receptor expression in human patients with biliary atresia (Li et al, 2011), primary biliary cirrhosis, primary sclerosing cholangitis, hepatitis C infection, and autoimmune hepatitis (Landi et al, 2014), no previous studies have directly investigated the causal relationships between type-2 cytokine-driven fibrosis and DR.…”
Section: Introductionmentioning
confidence: 99%